Lalo, Eduardo. Simone. 1 Ed. Colección Archipiélago Caribe. Nº 1. Buenos Aires: Corregidor, 2011. 208 p. - Doti, Pablo (Cuadernos del CILHA, 2015)
Reseña de la obra de Eduardo Lalo: Simone. 1ª Ed. Colección Archipiélago Caribe. Nº 1. Buenos Aires: Corregidor, 2011. 208 p.